2019
DOI: 10.3390/ijms20143578
|View full text |Cite
|
Sign up to set email alerts
|

The Cytoskeleton of the Retinal Pigment Epithelium: from Normal Aging to Age-Related Macular Degeneration

Abstract: The retinal pigment epithelium (RPE) is a unique epithelium, with major roles which are essential in the visual cycle and homeostasis of the outer retina. The RPE is a monolayer of polygonal and pigmented cells strategically placed between the neuroretina and Bruch membrane, adjacent to the fenestrated capillaries of the choriocapillaris. It shows strong apical (towards photoreceptors) to basal/basolateral (towards Bruch membrane) polarization. Multiple functions are bound to a complex structure of highly orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 153 publications
(167 reference statements)
5
53
0
Order By: Relevance
“…The two extracellular loops of occludin mediate adhesion of adjacent cells and block the movement of plasma components. The C-terminal domain combines directly with ZOs, subsequently interacting with the actin cytoskeleton, which is essential to organizing and maintaining cell polarization ( Balda & Matter, 2016 ; Furuse et al, 1994 ; Shin, Fogg & Margolis, 2006 ; Tarau et al, 2019 ). Feng et al (2019) demonstrated that during EMT, the breakdown of TJs resulting from loss of claudin-1 causes ARPE-19 cells to lose their epithelial phenotype and transform into fibroblasts, promoting the development of PVR.…”
Section: Survey Methodologymentioning
confidence: 99%
“…The two extracellular loops of occludin mediate adhesion of adjacent cells and block the movement of plasma components. The C-terminal domain combines directly with ZOs, subsequently interacting with the actin cytoskeleton, which is essential to organizing and maintaining cell polarization ( Balda & Matter, 2016 ; Furuse et al, 1994 ; Shin, Fogg & Margolis, 2006 ; Tarau et al, 2019 ). Feng et al (2019) demonstrated that during EMT, the breakdown of TJs resulting from loss of claudin-1 causes ARPE-19 cells to lose their epithelial phenotype and transform into fibroblasts, promoting the development of PVR.…”
Section: Survey Methodologymentioning
confidence: 99%
“…Normal polarized RPE cells possess F-actin in the transcellular membrane microvilli, circumferential microfilament bundles, and basal infolding 49 . However, accumulating evidence has demonstrated irregular distribution of F-actin in aged human RPE and the RPE of AMD patients 50 . The cytoskeleton has also been shown to affect the distribution of apical surface area in epithelial sheets 51 .…”
Section: Generation Of Pure Functional Rpe Sheetsmentioning
confidence: 99%
“…The two extracellular loops of occludin mediate adhesion of adjacent cells and block the movement of plasma components. The C-terminal domain combines directly with ZOs, subsequently interacting with the actin cytoskeleton, which is essential to organizing and maintaining cell polarization (Balda & Matter 2016;Furuse et al 1994;Shin et al 2006;Tarau et al 2019). Feng et al (2019) demonstrated that during EMT, the breakdown of TJs resulting from loss of claudin-1 causes ARPE-19 cells to lose their epithelial phenotype and transform into fibroblasts, promoting the development of PVR.…”
Section: The Polarized Retinal Pigment Epithelial Cellmentioning
confidence: 99%